Keseimbangan Finansial Bank: Manajemen Modal Kerja, Inflasi, dan Suku Bunga - Lukman Hakim (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to examine the effects of working capital management, inflation, and interest rates on the financial health of banks in Indonesia during the 2019–2023 period. Employing an associative quantitative approach, the research utilizes panel data from 20 conventional banks listed on the Indonesia Stock Exchange (IDX). The analysis applies the Fixed Effect Model (FEM) as the most appropriate estimator, as determined by the Chow and Hausman tests. The regression results indicate that the Current Ratio exerts a significantly positive influence on CAMEL scores, demonstrating the crucial role of liquidity in strengthening financial health. In contrast, inflation and interest rates have significant negative impacts, suggesting that macroeconomic volatility undermines banking performance. Additional control variables such as firm size, leverage measured by Debt-to-Equity Ratio (DER), and operational efficiency proxied by BOPO also exhibit significant relationships with financial health. The coefficient of determination (R²) of 68.2% implies that the independent variables collectively explain the majority of the variation in the banks’ financial conditions, while the remaining 31.8% is influenced by other external and internal factors not included in the model. These findings highlight the importance of effective liquidity management, prudent leverage, and operational efficiency in maintaining the stability and resilience of the banking sector. Moreover, the results emphasize the need for banks to adopt adaptive strategies to mitigate risks associated with inflationary pressures and interest rate fluctuations. This study provides useful insights for regulators, policymakers, and banking practitioners in formulating strategies to enhance financial stability and ensure sustainable growth in Indonesia’s banking industry.